2014
DOI: 10.1007/s00784-014-1185-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsurgical periodontal therapy (with or without oral doxycycline delivery) on glycemic status and clinical periodontal parameters in patients with prediabetes: a short-term longitudinal randomized case–control study

Abstract: NSPT (with and without oral doxycycline delivery) reduces hyperglycemia and periodontal inflammation in patients with prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 36 publications
5
41
3
1
Order By: Relevance
“…Nonsurgical periodontal therapy (such as plaque and calculus debridement using ultrasonic hand instruments) contributes toward minimizing oral soft tissue inflammation. [24][25][26] The biannual visits to oral healthcare providers may also have encouraged the participants in both groups to routinely maintain their oral hygiene status. It is therefore likely that regular oral hygiene maintenance contributed toward maintaining a healthy peri-implant soft tissue status and minimizing ABR around short implants in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical periodontal therapy (such as plaque and calculus debridement using ultrasonic hand instruments) contributes toward minimizing oral soft tissue inflammation. [24][25][26] The biannual visits to oral healthcare providers may also have encouraged the participants in both groups to routinely maintain their oral hygiene status. It is therefore likely that regular oral hygiene maintenance contributed toward maintaining a healthy peri-implant soft tissue status and minimizing ABR around short implants in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is hypothesized that the severity of periodontal disease is worse in prediabetic females compared to males with prediabetes. In a recent study, Javed et al [20] showed that SRP reduces hyperglycemia and periodontal infl ammation in patients with prediabetes. Moreover, studies [4,[21][22][23] have also reported that periodontal infl ammation is worse in smokers and individuals using smokeless tobacco products as compared to individuals not using tobacco in any form.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is hypothesized that the chronic periodontitis (CP) is worse in prediabetic females compared to males with prediabetes. In a recent study, Javed et al [21] showed that SRP reduces hyperglycemia and periodontal infl ammation in patients with prediabetes. Moreover, studies [22][23][24] have also shown that.…”
Section: Discussionmentioning
confidence: 99%